Consumption of dairy products in northern Nigeria - Jansen, G.P. (International Livestock Centre for Africa, 1992)
Gives justification for studying dairy consumption in Nigeria. General patterns of acquisition and consumption of dairy products are discussed with reference to domestically produced dairy products (fresh milk, sour milk, yoghurt, butter & cheese) and imported and derived dairy products (evaporated milk, package liquid milk, baby formulae, yoghurt, ice-cream, butter, cheese & margarine) and frequency of consumption. Levels of dairy product consumption and their determinants are listed. Structure of dairy product consumption, factors influencing the demand for dairy products, and consumers preferences for dairy products are also examined.